Family Support and Medication Adherence in Patients in Prolanis Program - Aini, Zahratul; Suardi, Hijra Novia; Dewi, Fitria Meutia; Ibrahim, Tilaili; Waraztuty, Ika; Mulia, Vera Dewi (Majalah Kedokteran Bandung, 2025)
The Chronic Disease Management Program, or Program Pengelolaan Penyakit Kronis (Prolanis), is a disease management program designed for individuals with chronic illnesses. It aims to maintain health and improve quality of life. The success of Prolanis depends not only on patient adherence to medication but also on family involvement as the primary source of support. This study aimed to examine the relationship between family support and medication adherence among Prolanis patients at Batoh Public Health Center, Banda Aceh, Indonesia. An observational analytic study with a cross-sectional design was conducted using consecutive sampling of 74 Prolanis participants. Data were collected through guided interviews. Among the participants, 33 individuals (44.5%) exhibited low medication adherence, while 41 individuals (55.5%) demonstrated high adherence. Additionally, 8 participants (10.8%) reported poor family support, whereas 66 participants (89.2%) received good family support. Data analysis using the chi-square test revealed a significant relationship (p=0.009) between family support and medication adherence. Therefore, it can be concluded that family support is significantly associated with medication adherence in Prolanis patients.  Families are the main supporters in maintaining the health of their family members, with an important role in encouraging, supporting, and supervising patients' treatment. Good support and constant encouragement and attention can increase patients' confidence, which in turn will affect their adherence to treatment.Correction Notice: A corrigendum has been published for the article “Family Support and Medication Adherence in Patients in the Prolanis Program.” The corrigendum is available at: https://doi.org/10.15395/mkb.v57.4951